2012
DOI: 10.1371/journal.pone.0048695
|View full text |Cite
|
Sign up to set email alerts
|

A Nice Day for an Infection? Weather Conditions and Social Contact Patterns Relevant to Influenza Transmission

Abstract: Although there is no doubt that significant morbidity and mortality occur during annual influenza epidemics, the role of contextual circumstances, which catalyze seasonal influenza transmission, remains unclear. Weather conditions are believed to affect virus survival, efficiency of transmission and host immunity, but seasonality may also be driven by a tendency of people to congregate indoors during periods of bad weather. To test this hypothesis, we combined data from a social contact survey in Belgium with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(154 citation statements)
references
References 38 publications
8
145
0
1
Order By: Relevance
“…We first used the methods of Willem et al [10] to estimate the model-free estimates of relative change in R 0 and the number of contacts between weekdays and weekends. The relative change in the number of contacts also takes into consideration the number of contacts and the diary weight for each participant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first used the methods of Willem et al [10] to estimate the model-free estimates of relative change in R 0 and the number of contacts between weekdays and weekends. The relative change in the number of contacts also takes into consideration the number of contacts and the diary weight for each participant.…”
Section: Resultsmentioning
confidence: 99%
“…These factors affect influenza transmission because they may prolong the virus's survival, impede the human immune system, or enhance contact intensity among people [8][9][10]. These factors affect influenza transmission because they may prolong the virus's survival, impede the human immune system, or enhance contact intensity among people [8][9][10].…”
Section: Seasonal Variations In Infectious Diseases Have Long Been Rementioning
confidence: 99%
See 1 more Smart Citation
“…For the United States, absolute humidity was identified as a critical determinant of 24 observed influenza mortality (Barreca and Shimshack, 2012) and anomalously low humidity levels were found to precede the onset of increased wintertime influenza-related mortality in the United States by several weeks (Davis et al, 2012;Shaman et al, 2010). The respiratory impact of low atmospheric humidity was evident in other studies in Belgium (Lander et al, 2012), China (Xiao et al, 2013), Japan (Harata et al, 2004), Israel (Yaari et al, 2010), the Netherlands and Portugal (van Noort et al, 2012), and was inferred in forensic studies of major historical influenza outbreaks in England and Wales (He et al, 2013). Yet in studies that utilized relative humidity, Zhang et al (2013) found a negative association between RSV and Rodriguez-Martinez (2015) uncovered no relationship.…”
Section: Humidity and Pulmonary Diseasementioning
confidence: 87%
“…In certain high altitude regions, inclement weather may drive people indoors for longer periods of time 11 , increasing the length of the time individuals are exposed to indoor pollution 9 and/or social contacts with patients with ARI 12,13 . We have previously reported that in rural highland communities of the Peruvian Andes, social contacts that could facilitate the transmission of infections were very frequent and physical contacts appeared to be higher than in some other developing counties 14 .…”
Section: Introductionmentioning
confidence: 99%